Analisis Teknik Gerak Renang Gaya Kupu-kupu - Azzahra, Putri; M, Maidarman; Mardesia, Pringgo; Purnomo, Eko (Jurnal Gladiator, 2025)
This study aims to analyze the butterfly stroke technique of swimmers at Build SC, following initial observations that indicated weaknesses in mastering basic skills. A qualitative case study approach was employed, involving 13 purposively selected athletes from age groups I to III. Technical assessment was conducted using the Tec Pa (Technical Performance Assessment) instrument, focusing on six technical aspects: head position, body position, elbows, knees, ankle joints, and coordination. Data were analyzed using Miles and Huberman’s interactive model, with data validity ensured through triangulation. The results reveal that most athletes have mastered several technical components, such as movement coordination, body position during the pull phase, and elbow transition. However, weaknesses remain in head position during breathing, body position in streamline, as well as catch and kick techniques, which collectively impact overall movement efficiency. Keywords : Butterfly Stroke, Technical Analysis, swimming Technique, Tec Pa